1936
DOI: 10.1017/s002185960002308x
|View full text |Cite
|
Sign up to set email alerts
|

The nutrition of the bacon pig. I. The influence of high levels of protein intake on growth, conformation and quality in the bacon pig

Abstract: The present practice of basing payment for bacon pigs not merely on carcass weight, but also on carcass quality as expressed in the factory grading results, has led necessarily to an enlargement of outook on the part of the investigator in the domain of swine nutrition. The interest of the experimenter in the past has tended to be restricted to such questions as the influence of nutritional factors on the rate of live-weight increase and the efficiency of food conversion, the problem of how feeding may influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

1943
1943
1989
1989

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 0 publications
4
25
1
Order By: Relevance
“…These observations are in agreement both qualitatively and quantitatively with comparisons between sexes which have been reported previously (e.g. Lacy, 1932;Murray, 1934;Woodman et al 1936;Warner, Ellis & Howe, 1934;Callow, 1938;McMeekan, 1940;Crampton, 1941;Bennett & Coles, 1946;Johansson & Korkman, 1951;Harrington & Pomeroy, 1955;Fredeen, Bowman & Stothart, 1955 o, 6). In Exp.…”
Section: Carcass-quality Measurementssupporting
confidence: 92%
See 3 more Smart Citations
“…These observations are in agreement both qualitatively and quantitatively with comparisons between sexes which have been reported previously (e.g. Lacy, 1932;Murray, 1934;Woodman et al 1936;Warner, Ellis & Howe, 1934;Callow, 1938;McMeekan, 1940;Crampton, 1941;Bennett & Coles, 1946;Johansson & Korkman, 1951;Harrington & Pomeroy, 1955;Fredeen, Bowman & Stothart, 1955 o, 6). In Exp.…”
Section: Carcass-quality Measurementssupporting
confidence: 92%
“…Gregory & Dickerson (1952) also reported that restricted feeding increased the lean content of the carcass, and Crampton (1938) and Crampton & Ash ton (1945) found that slower growth was associated with larger 'eye' muscles, although in the first of these papers the effect was very small. However, there have also been reports that larger 'eye' muscles are associated to some extent with faster growth, although the correlation just failed to be significant (Woodman, Evans, Callow & Wishart, 1936); that increase in rate of growth results in increasingly heavy psoas muscles (Callow & Dunlop, 1934); that there is no significant correlation between rate of gain before 100 lb. and area of 'eye' muscle (Crampton, 1940); and that the breadth of the ' eye' muscle is resistant to modification by growth rate (Donald, 1940).…”
Section: A B C a B C A B A S Essexmentioning
confidence: 99%
See 2 more Smart Citations
“…It was indicated in a previous publication in this Journal (Woodman & Evans, 1936) that an individual-feeding trial may be four times as accurate as a corresponding group-feeding trial, since the standard error of each pig's live-weight gain in the former is only 6-5 % of the mean live-weight gain, whereas the value for the group trial may be as large as 12-5 %. Precision is measured in terms of the square of the standard error.…”
mentioning
confidence: 98%